Faktor-faktor yang Berhubungan dengan Kejadian Disminorhea Primer pada Siswi SMA Pembina Palembang Tahun 2022 - Puput Dwi Rahayu; Rizki Amalia; Eka Rahmawati; Suprida Suprida (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Primary dysmenorrhea is menstrual pain that is found without significant abnormalities of the genital organs, the influencing factors are the age of menarche, the length of menstruation, exercise habits and family history. The purpose of this study was to determine the relationship between age at menarche, length of menstruation, exercise habits and family history with the incidence of primary dysminorhea in high school students Pembina Palembang. The research method uses an analytical survey with a cross sectional approach. Where is the independent variable (age of menarche, duration of menstruation, exercise habits and family history) and the dependent variable (incidence of primary dysminorhea). The research population is all students of SMA Pembina with a sample of 57 respondents. Data were analyzed using univariate and bivariate methods. This study uses primary data. The results of data analysis obtained p value of 0.02 <0.05 so that statistically there was a relationship between age of menarche and the incidence of primary dysmenorrhea, p value of 0.02 <0.05 so that statistically there was a relationship between the length of menstruation and the incidence of primary dysmenorrhea. p value 0.03 <0.05 so statistically there is a relationship between exercise habits and the incidence of primary dysmenorrhea, p value 0.004 <0.05 so statistically there is a relationship between family history and the incidence of primary dysmenorrhea. It can be concluded that there is a relationship between age of menarche, length of menstruation, exercise habits and family history simultaneously with the incidence of primary dysmenorrhea.